THE LOCAL KNOWLEDGE TRANSFER BASED ON CONTINUOUS IMPROVEMENT IMPLEMENTATION AT SMEs GROUP - Elin Herlina; Deden Syarifudin; Risna Kartika (Journal of Management Review, 2019)
This Paper is addressed to developing a knowledge transfer in the local contexed to implementation of continuous improvement (CI) on SMEs. The main problem of the research is how to developing the knowledge transfer model in the implementation of continuous improvement (CI) on SMEs in location at District of Cikoneng, Ciamis Regency. The concept of knowledge management and CI often cannot be rooted in local culture and knowledge, on the other hand it is more valuable to be implemented and evaluated in large companies than SMEs. However local knowledge is very valuable for local residents in increasing knowledge transfer and continuous improvement. Using a case study research approach, we managed to uncover the fact that local knowledge needs to be institutionalized to improve the sustainability of the company. There is a different work orientation and process between male and female employees, where men pay more attention to structured instruction compared to more informal women with different productivity. The CI model implemented must consider the process of their understanding and based on local knowledge, so that changes in mindset occur naturally can be found changes.